The Impact of Different Media Materiality on the Creative Process - Fauzan Sidik, Muhamad; Damayanti, Nuning Yanti; Mutiaz, Intan Rizky; Grahita, Banung (Journal of Visual Art and Design, 2024)
As a complex phenomenon, the creative process is shaped by multiple factors such as emotions, cognitive abilities, and contexts. Media materiality, as one of the contextual aspects of the creative process, has a significant impact on shaping and informing creative outcomes. To better understand the impact of different media materiality on the creative process, nineteen published studies were analyzed adhering to the PRISMA guidelines, focusing on four comparison groups: physical media vs non-immersive 2D/3D media, physical media vs immersive 3D media, digital 2D media vs immersive 3D media, and non-immersive 3D media vs immersive 3D media. The findings suggest that the choice of media materiality significantly influences the creative process, impacting factors such as ideation, expression, collaboration, and the overall experience of creating. This review concluded that media materiality in immersive virtual reality has the potential to enhance creativity, but traditional media may have more significant psychological benefits compared to virtual reality experiences. Future research directions in fine arts and design will be discussed based on the review results.